Influence of Monensin and Diflubenzuron on the Control of Immature Horn Fly and House Fly (Diptera: Muscidae) and Chemical Composition of Cattle Feces. Issue 2 (20th December 2022) - Sanchez-Sandoval, U A; Figueroa-Zamudio, J J; Ramirez, J; Walker, H L; Löest, C A; Soto-Navarro, S A; Smythe, B G
Abstract: Twelve Angus × Hereford crossbred heifers were used in a completely randomized design to evaluate the effects of monensin and diflubenzuron feed additives on horn fly ( Haematobia irritans ) (L.) and house fly ( Musca domestica ) (L.) immature development. Heifers were randomly assigned to one of four treatment groups; 1) monensin fed at label rate, 2) diflubenzuron fed at label rate, 3) monensin and diflubenzuron fed at label rates together, and 4) nonsupplemented control. All treatments were administered from SD 0 to 28, followed by a 16-d wash-out period for a total study duration of 45 d and assayed to assess adult fly emergence, as well as fecal pH and fecal bacterial and total protein. A treatment × day interaction ( P < 0.01) was observed for adult fly emergence. Fly emergence was not affected ( P ≥ 0.05) by monensin, but was reduced during the 28 d treatment period when diflubenzuron was present ( P = 0.01). Fecal pH, fecal bacterial protein, and total protein were not affected by any of the treatments ( P ≥ 0.13). It is concluded that diflubenzuron is effective against both horn and house fly development regardless of the presence of monensin.